Evaluating Skeletal Trauma and Forensic Anthropology for Medicolegal Investigations: A Systematic Review (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: Skeletal trauma analysis is crucial in the area of forensic anthropology for locating and analyzingwounds in human remains. For the evaluation and recording of bone injuries, a number of techniques and methodshave been developed over the years, including ocular examination and cutting-edge imaging modalities. In orderto determine the approaches used in diagnosing bone trauma, the goal of this systematic review is to criticallystudy the body of current research. The goal of this study is to draw attention to the advantages, disadvantages,and recent technological developments of these techniques.Aim: This study thoroughly examines the examination of skeletal trauma and the function of forensic anthropologyin medicolegal cases, finding knowledge gaps and outlining potential directions for future research.Method: To find relevant studies released within a certain timeframe, a thorough search across the largest scientificdatabases was carried out. Studies on the assessment of skeletal trauma and the use of forensic anthropology inmedicolegal cases were also included. For methodological rigor, quality, and applicability, the chosen papersunderwent careful evaluation. According to the particular approaches and procedures used in assessing skeletaltrauma and the contributions of forensic anthropology to the field, data were retrieved, synthesized, and classified.Conclusion: This systematic study examines several approaches for assessing skeletal injuries in medicolegalinvestigations, stressing their benefits and drawbacks as well as the function of forensic anthropology. For thisdiscipline to improve accuracy and validity, advancements, established standards, and cutting-edge technologyare essential.
Keywords: anthropological identification, bone fractures, forensic anthropology, medicolegal investigations, forensic evidence etc